Faktor Sosial Pengembangan Bahasa Arab - Ummah, Khaira; Yasmadi (Ukazh : Journal of Arabic Studies, 2025)
The development of the Arabic language today is strongly influenced by the social dynamics of its speakers. Globalization, the rapid flow of information, digital technology, population mobility, language policy, and education systems have all contributed to changes in vocabulary, dialect variation, and the functional use of Arabic across various domains. This research employs a descriptive qualitative method with a sociolinguistic approach through library research based on academic literature from the past ten years. Content analysis was used to identify, classify, and interpret data related to the influence of social factors on the development of the Arabic language. The findings show that social media has produced new terms such as taṭbīq (application), mutābi‘ūn (followers), i‘jāb (like), and musyārakah (share); education maintains the use of Arabic fusha through curricula and academic terminology such as al-ta‘allum al-iliktrūnī (e-learning) and al-faṣl al-iftiṛāḍī (virtual classroom); migration generates diaspora dialects and code-mixing, such as blends of Arabic with French or local Asian languages; language policy supports the preservation of fusha through standardized terminology such as ḥāsūb (computer); and economic and cultural globalization drives the adoption of new expressions such as al-tijārah al-‘ālamiyyah (global trade) and al-siyāḥah al-iliktrūniyyah (e-tourism). These findings affirm that social factors not only shape linguistic adaptation, but also sustain the vitality of Arabic in educational, religious, popular culture, and global communication contexts.